Perancangan Interior Perpustakaan Umum di Surabaya - Gunawan, Yustin Anggraeni (Intra, 2013)
The library is a room, part of a building, or the building itself, which is used for storage of books and other publications are normally stored according to specific arrangements to use the reader, not for sale. The design of the public library is intended to serve the general bulic as means of lifelong learning, regardless of age, gender, ethnicity, race, religion, and social-economy status. Facility to be made photocopy and print area, audio visual room, reading area, shelves of books, magazines and newspaper racks. Its design concept is to create an atmosphere that is fresh, natural, clean, comfortable, open, and creation. Therefore, the theme of which is âThe Window of Surabayaâ